2016
DOI: 10.1093/gji/ggw467
|View full text |Cite
|
Sign up to set email alerts
|

GNSS related periodic signals in coordinate time-series from Precise Point Positioning

Abstract: In Global Navigation Satellite System (GNSS) coordinate time-series unrecognized errors and unmodelled (periodic) effects may bias nonlinear motions induced by geophysical signals.Hence, understanding and mitigating these errors is vital to reducing biases and on revealing subtle geophysical signals. To assess the nature of periodic signals in coordinate time-series Precise Point Positioning (PPP) solutions for the period 2008-2015 are generated. The solutions consider Global Positioning System (GPS), GLObalna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…However, these results cannot exclude the possibility that the draconitic signal is partly due to site-specific effects as suggested by King and Watson [16] because there are still several peaks visible at the frequencies of the draconitic harmonics and the estimation of the power spectrum has uncertainty. Moreover, these results are consistent to the conclusions of Abraha et al [17].…”
Section: Characteristics Of the Draconitic Harmonicssupporting
confidence: 93%
“…However, these results cannot exclude the possibility that the draconitic signal is partly due to site-specific effects as suggested by King and Watson [16] because there are still several peaks visible at the frequencies of the draconitic harmonics and the estimation of the power spectrum has uncertainty. Moreover, these results are consistent to the conclusions of Abraha et al [17].…”
Section: Characteristics Of the Draconitic Harmonicssupporting
confidence: 93%
“…There is no single peak visible in the periodogram but rather a broad range of peaks close to each other. Abraha et al (2017) already indicated that these might be associated with the changing number of satellites in the constellation on the example of GLONASS. In the analyzed period, the number of available GPS, GLONASS, and Galileo satellites was constant within ±2 satellites day by day (Figure 1).…”
Section: Assessment Of the Differences Between System-specific Daily ...mentioning
confidence: 99%
“…GPS observations from January 01, 2014, to December 31, 2018 are available from the Scripps Orbit and Permanent Array Center (SOPAC). The GPS observations were processed by the standard procedures of Bernese GNSS software version 5.2 (http://www.bernese.unibe.ch/docs/DOCU52.pdf) in kinematic PPP mode into ambiguity-float solutions [27]. The sample interval is 10min, the elevation cut-off angle is 3°.…”
Section: B Gps Data Preprocessingmentioning
confidence: 99%